PELATIHAN MENULIS CERPEN UNTUK SISWA MADRASAH ALIYAH RAUDHATUSYUBBAN - Sri Normuliati; Istiqamah Istiqamah (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2019)
This service aims to improve the ability to write short stories for students of Madrasah Aliyah Raudhatusyubban using characterization techniques and three-word strategies. The method of activities used in this service is in the form of training / workshops and the results of the training are in the form of short paragraphs about short stories made. The training participants were 38 students from Aliyah Raudhatusyubban Madrasah.The results of the service show that students have an interest in the field of writing short stories but are constrained by ignorance in expressing ideas. The training of writing short stories using characterization techniques and three-word strategies is expected to be a solution for students to improve their ability to write short stories.